Influence of the suckling on the reproductive and productive performance of Zebu cows - Bacalhau, Augrizônio dos Santos; dos Santos, Elson Soares; Albuquerque, Rômulo Pontes de Freitas (Pesquisa Agropecuaria Brasileira, 1994)
The effect of the suckling in reproductive and productive efficiency of Zebu cows, (77 Gyr cows and 72 Guzera cows) was evaluated in the treatments: Experimental and Traditional. The average of interval to first post-partum service (IPPE), service period, cow weight at fertilization (PVF), weaning weight (PCD), lactation length and milk yield were 133 days, 145 days, 387.2 kg, 164.9 kg, 282 days and 2,202 kg (Gyr herd) 92 days, 122 days, 423.2 kg, 184.2 kg, 273 days and 2,314 kg (Guzera herd). The reproductive and productive performance of Gyr herd were not affected by suckling; however, the suckling had significative influence on IPPE, lactation length and milk yield of Guzera herd. Season of the year showed a significant effect on IPPE, on the service period and PCD, and birth year on PCD and lactation length, in Gyr herd, but it dit not influence on the characteristics studied in Guzera herd. The PVF and milk yield of Gyr cows as well as the IPPE and lactation length, of Guzera cows were influenced significantly by the parturition order.